MORFOLOGI TANAH DAN SIFAT FISIKA TANAH PADA LAHAN BERVEGETASI JATI (Tectona grandis) DAN UBI KAYU (Manihot esculenta Crantz) DI DESA KARANG SARI JATI AGUNG LAMPUNG SELATAN - Cici Chintia Sari; Didin Wiharso; Nur Afni Afrianti (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2022)
Cassava is a plant that has an important role for the survival of the community, but its existence is often considered to damage agricultural land. The intensive soil system is considered to accelerate land degradation, and teak with a minimum tillage system is considered to be more friendly to the soil. The purpose of this study was to identify the morphology and physical properties of the soil on land planted with cassava in monoculture and teak as a result of the different land use patterns. This research was conducted on community land in Karang Sari Village, Jati Agung District, South Lampung Regency. showed that the soil color of cassava and teak tended to be the same.